2012
DOI: 10.1186/1756-8722-5-42
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of SRSF1 and PRMT1 expression with clinical status of pediatric acute lymphoblastic leukemia

Abstract: BackgroundAcute lymphoblastic leukemia (ALL) is the most frequently-occurring malignant neoplasm in children, but the pathogenesis of the disease remains unclear. In a microarray assay using samples from 100 children with ALL, SFRS1 was found to be up-regulated. Serine/arginine-rich splicing factor 1 (SRSF1, also termed SF2/ASF), encoded by the SFRS1 gene, had been shown to be a pro-oncoprotein. Our previous study indicated that SRSF1 can be methylated by protein arginine methyltransferase 1 (PRMT1) in vitro; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 34 publications
5
42
0
1
Order By: Relevance
“…They have been found to be aberrantly expressed in many cancer types, including lung, ovary, and breast tumors. 17,18,21 In this study, we also provided similar evidence of SRSF1-HMws and SRSF3 overexpression in primary cervical cancer using an adequate number of samples. Although the up-regulation incidences (69%Y66%) and diagnostic accuracies (72%Y75%) of SRSF1-HMws and SRSF3 in cervical cancer were lower than those of HNRNPA1, SRSF1-HMws and SRSF3 are still worth considering as tumor markers for cervical cancer, as they showed results comparable to those of CEA, a commonly used tumor marker with acceptable diagnostic rates of accuracy.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…They have been found to be aberrantly expressed in many cancer types, including lung, ovary, and breast tumors. 17,18,21 In this study, we also provided similar evidence of SRSF1-HMws and SRSF3 overexpression in primary cervical cancer using an adequate number of samples. Although the up-regulation incidences (69%Y66%) and diagnostic accuracies (72%Y75%) of SRSF1-HMws and SRSF3 in cervical cancer were lower than those of HNRNPA1, SRSF1-HMws and SRSF3 are still worth considering as tumor markers for cervical cancer, as they showed results comparable to those of CEA, a commonly used tumor marker with acceptable diagnostic rates of accuracy.…”
Section: Discussionsupporting
confidence: 72%
“…Relative protein levels of the samples were determined after normalization to the A-actin band and calibrated using bands from the study-defined standard sample on each membrane. As presented in previous reports 18,19 and/or manufacturers' instructions, HNRNPA1, SRSF1, and SCCA showed multiple bands in each target molecular weight area. For HNRNPA1 and SCCA, the sum of the distinct band/bands was then analyzed for the proteins.…”
Section: Protein Extraction and Semiquantitative Immunoblottingsupporting
confidence: 63%
“…Previously, we reported that arginine methylation was associated with B cell leukemia; another two reports also provided data on roles during B cell development and lymphoma genesis (29)(30)(31). Given that histone arginine methylation was a common posttranslation modification and that arginine methylation deficiency by PRMTs knockout in mice led to abnormal development (14), we generated PRMT7-knockout mice by gene targeting (Supplemental Fig.…”
Section: Prmt7 Was Preferentially Expressed In Immune Tissuesmentioning
confidence: 99%
“…106 The following primer pairs were used: human DDAH II (5 0 -GATCTG 107 GCCAAAGCTCAAAG-3 0 forward and 5 0 -CAACCCAGGACGAAGAAA 108 GA-3 0 reverse) [14]; mouse DDAH II (5 0 -GGTTGATGGAGTG CGT 109 AAAGC-3 0 forward and 5 0 -TCCACAATTCGGAGTCCCAA-3 0 reverse) 110 [15]; human GAPDH (5 0 -CTGCTCCTCCTGTTCGACAGT-3 0 forward 111 and 5 0 -CCGTTGACTCCGACCTTCAC-3 0 reverse) [14]; mouse GAPDH 112 (5 0 -GAGAATG GGAAGCTTGTCATC-3 0 forward and 5 0 -GTCCAC-113 CACCCTGTTGCTGTA-3 0 reverse) [1]; human PRMT I (5 0 -GATGCT-114 GAAGGACGAGGTGC-3 0 forward and 5 0 -ACTCGATCCCGATGACCTTG 115 CG-3 0 reverse) [17]; mouse PRMT I (5 0 -AATGGGATGAGCCTCCAGC-116 3 0 forward and 5 0 -TGCTTGGCCACAGGAAACTT-3 0 reverse) [18]. The 117 relative abundance of PRMT I/GAPDH or DDAH II/GAPDH in control 118 group was expressed as 100% for comparative purposes.…”
mentioning
confidence: 99%
“…The 124 Western Blotting of PRMT I and DDAH II expressions were carried 125 out as described previously [17][18][19][20]. 182 Using linear regression from log concentration-effect curves, the half-183 maximal relaxation (EC50) reply to acetylcholine was evaluated.…”
mentioning
confidence: 99%